ANALISIS SOLVABILITAS DAN PROFITABILITAS PADA PERUSAHAN FOOD AND STAPLES RETAILING - Rahmawati, Iin; Rio, Maulana Arief (POLITEKNIK LP3I JAKARTA, 2025)
Manufacturing companies still have an influence on the Indonesian economy. Most people will of course be related to food and retail companies. This research was conducted to analyze the solvency and profitability ratios. The research method of this research is a type of non-statistical quantitative research. The data in this research was taken from food and staples retailing sub-sector companies listed on the Indonesia Stock Exchange (BEI) from 2022 to 2024, which are in the Food and Staples Retailing sub-sector companies. The results of the solvency ratio analysis show that the DAR ratio of the company that has the largest decreasing trend in DAR is BUAH in 2021-2022 at 25.11% and in 2022-2023 MIDI at 11.36% and in 2023-2024, namely PCAR at 7.24%. The company's DER ratio with the largest downward trend in this ratio is WICO in 2023-2024 of 5,637.78%, PAYA in 2023-2024 of 2,134.90% and MPPA in 2022-2023 of 546.79%. In terms of profitability ratios, the company with the highest ROA value is the HERO company of 16.21% in 2022-2023, MPPA of 4.34%, RANC in 2023-2024 of 11.95 and DAYA of 7.03%. The highest ROE in 2021-2022 is the HERO company at 116.57%. In 2022-2023 the MPPA company will be 160.26% and in 2023-2024 the WICO company will be 2051.93%.